In a mirror, darkly: a comparison of Chinese and Japanese military reform, 1860-1894 - Graham, James Mark (Kansas State University, 2019)
By the year 1860, both the Qing dynasty in China and the Tokugawa Shogunate in Japan were under considerable strain following Western intervention and domestic disturbances. While the Qing were able to survive the disturbances, the Tokugawa Shogunate did not, and was replaced by a government of the Tokugawa’s clans’ enemies, under the nominally direct leadership of the Meiji emperor. Both Chinese and Japanese leaders recognized that reform of their societies was necessary to ensure their independence with a special emphasis on military reform. As a result, both the Qing dynasty and the Meiji government sought out and employed Western military advisors to assist their efforts. There are similarities between how the Chinese and Japanese used their western advice, namely that both insisted on maintaining control over their advisors, ensuring that they would serve the desires of their respective governments. However, the differences were greater both in number and severity. The Chinese employment of western advisors was based on regional and provincial interests. Additionally, the Qing focused much more on the acquisition of Western technology. The Japanese used a formal system of official military advisory missions, whereas the Chinese preferred to employ individuals informally on a contract basis. All of these sources of similarities and differences were almost exclusively due to domestic politics, rather than any desire of a foreign power. For Qing China, it was vitally important to maintain the security of the dynasty, and they feared a powerful centralized military would overthrow them. For the Japanese, it was about creating a reliable military to ensure the survival of the Meiji regime. While both governments experienced some success, in the battlefields of Korea and northern China, it was the Japanese model that ultimately prevailed.
Keywords: China; Japan; Military reform; Qing; Meiji; Military